Studi Analisis Penggunaan Alat Berat (Crane) Sebagai Alat Angkat Untuk Instalasi Vessel LP Dan HP Separator Proyek PLTP Rantau Dedap. - Agust Harry Widodo Putro (Jurnal Aplikasi Teknik Sipil, 2022)
Lifting works are included in the group of high-risk work where there are many potential risks of work accidents that may occur. This is the background for conducting research on the use of cranes in lifting work for intstallation of vessel LP (Low Pressure) and HP (High Pressure) Separator for PLTP Rantau Dedap project. The research on the analysis of lifting work carried out is the comparison of construction methods using crawler cranes and mobile cranes to achieve a lifting operation plan that can take place properly and safely at a cost that is within the budget because it meets the criteria of applicable regulations and standards. This research aims to determine the right type of crane for lifting works. It is hoped that in the future it can prevent work accidents on lifting works so that it can increase work productivity, on time according to work schedules and company profits. The results show that the lifting work at the Rantau Dedap PLTP project is more appropriate when using a crawler crane.